2019
DOI: 10.1108/rpj-06-2017-0116
|View full text |Cite
|
Sign up to set email alerts
|

SLM process parameters development of Cu-alloy Cu7.2Ni1.8Si1Cr

Abstract: Purpose Materials with a high thermal conductivity, such as Cu-alloys hold the most interest to the plastic moulding industry. Additive manufacturing (AM), especially selective laser melting (SLM) of metals, allows the production of parts with complicated internal cooling and increased production efficiency. The portfolio of alloys for metal AM is limited and still missing process parameters for the processing of copper alloys. This paper aims to preview the process parameters of high-strength alloy Cu7.2Ni1.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
2
12
0
1
Order By: Relevance
“…Similar results were found in Cu-Cr alloys with Cr contents by 20 wt.% and 25 wt.% [30]. For a Cu7.2Ni1.8Si1Cr provided by Sandvik Osprey Ltd., a relative density of 99.9% without any cracks was achieved [31].…”
Section: Introductionsupporting
confidence: 81%
“…Similar results were found in Cu-Cr alloys with Cr contents by 20 wt.% and 25 wt.% [30]. For a Cu7.2Ni1.8Si1Cr provided by Sandvik Osprey Ltd., a relative density of 99.9% without any cracks was achieved [31].…”
Section: Introductionsupporting
confidence: 81%
“…Thin walls of varying thicknesses (from 0.4 mm to 3 mm) were successfully produced from C18400 copper alloy with a relative density of 96.74 % under proper forming parameters [4]. Paloušek et al [11] and investigated process parameters of Cu7.2Ni1.8Si1Cr copper alloy. Klimek [12] studied the influence of SLM process parameters on the wall thickness and surface quality.…”
Section: Capability Of Copper Thin-wall Structures Produced By Slmmentioning
confidence: 99%
“…The copper powder Cu7.2Ni1.8Si1Cr was produced by Sandvik Osprey Ltd. The powder morphology was evaluated in the study of Paloušek et al [11] based on the laser diffraction analysis and showed mainly a spherical shape of the particles. The powder particles had a large variability in size with an average value of 22.9 μm and 90 % were up to 38.6 μm.…”
Section: Copper Powdermentioning
confidence: 99%
See 2 more Smart Citations